Ethnobioconservation with a Predict, Observe, Explain (POE) Strategy Against Student Cooperative Skills - Pamella Mercy Papilaya; Prelly Marsell Jolanda Tuapattinaya (Postgraduate, University of Mataram, 2022)
Student cooperative skills are an internal representation of the conceptual understanding of Maluku's natural resource conservation biology. Currently, students still have difficulty explaining the relationship between biological conservation and biological, physical and chemical conditions of a natural resource phenomenon, at a concrete level. These difficulties require research, through Predict, Observe, Explain (POE) Strategy, Ethnobioconservation Development of Maluku Natural Resources. This study aimed to reveal the development and differences in students' cooperative skills after learning Bioconservation with POE and conventional learning. Indicators of students' cooperative skills were adapted from Johnson, & Holubec, (2002). The topic of Maluku Natural Resources Ethnobioconservation combined with the POE Strategy consists of five topics, namely 1) Burning rocks in Maluku Tenggara Barat Indonesia; 2) Sasi Lompa Opening Ceremony in Haruku Village, Maluku Indonesia; 3) Timba Laor, Latuhalat Village, Ambon Maluku Indonesia; 4) Meti Kei Ceremony in Southeast Maluku Indonesia; and 5) The Opening Ceremony of Sasi Teripang in Noloth Village, Saparua Island, Maluku Indonesia. The findings indicated that the POE strategy resulted in better student cooperative skills. The N-Gain scores of students in the class using the POE and conventional strategies were found to be 71.43 and 47.73, respectively. Meanwhile, the value of coopetarif skills was higher (36.67%) compared to conventional learning. Thus, it can be concluded that POE Strategy learning is effective in increasing the cooperative skills of students. This research recommends that POE is very important and useful for use in biology learning. because the POE strategy facilitates student concept change